The Effectiveness of Vocabulary Mastery and Grammar Management on English Description Text Writing Skills - Kunah Kunah; Supriyani Supriyani (JELL (Journal of English Language and Literature) STIBA-IEC Jakarta, 2024)
This study is an attempt to determine the effect of vocabulary and grammar management on English description text writing skill at SMKN 1 Indramayu. This research is to answer the questions: 1) How are the students’ writing skills at SMKN 1 Indramayu? 2) How is the influence of students’ descriptive text writing skills at SMKN 1 Indramayu? 3) How effective is vocabulary to improve English description text writing skills at SMKN 1 Indramayu? 4)How effective is grammar management to improve English description text writing skills at SMKN 1 Indramayu? The method used is survey. The inference analysis used is descriptive correlational research and multiple linear regression. The population in this study was 266 and a sample 70 respondents were taken from grade XI. The results of this study are proven by the acquisition of Sig. = 0.000 <0.05 and F observe = 192,939. 2) There is a significant effect of vocabulary mastery on English descriptive text writing skills, this is proven by the acquisition of Sig. = 0.000 <0.05 and T observe = 10,831. 3) There is a significant effect of grammar mastery o English descriptive text writing skills, this is proven by the acquisition of Sig. 0.000 <0.05 and T observe = 6.984.